The hybrid lipoplex induces cytoskeletal rearrangement via autophagy/RhoA signaling pathway for enhanced anticancer gene therapy - Xueyi Hu; Yichun Wang; Ruohan Wang; Yiyao Pu; Rongrong Jin; Yu Nie; Xintao Shuai (Nature Communications)
Abstract Delivering plasmid DNA (pDNA) to solid tumors remains a significant challenge due to the requirement for multiple transport steps and the need to promote delivery efficiency. Herein, we present a virus-mimicking hybrid lipoplex, composed of an arginine-rich cationic lipid, hyaluronic acid derivatives coated gold nanoparticles, and pDNA. This system induces cytoskeletal rearrangements through “outside-in” mechanical and “inside-out” biochemical signaling, overcoming intra- and intercellular barriers to enhance pDNA delivery. By modulating autophagy, RhoA signaling, and cytoskeletal dynamics, we achieve a 20-fold increase in gene expression with high tissue specificity in solid tumors. Furthermore, the system is applied to co-deliver a p53 plasmid and an MDM2 inhibitor, demonstrating significant synergistic antitumor effects in hepatocellular and lung carcinomas.